Pengelolaan Sayur Tomat Menjadi Manisan Desa Liprak Wetan Kecamatan Banyuanyar Kabupaten Probolinggo - Rahayu, Eka; Zahro , Aminatuz; Nur Aini , Putri; Hidayati , Nur; Bainana , Ulin; Istianah Putri, Nur; Faizatur Rohma , Nur (Najah: Journal of Research and Community Service, 2024)
Field Work Activities (KKN) are field activities for students that must be carried out, this activity aims to increase student empathy regarding conditions in society. The 2023 UNZAH KKN takes place in Liprak Wetan Village, Banyuanyar District, Probolinggo Regency. In this activity we analyze the processing of tomatoes into candied tomatoes. This tomato management was the first experiment conducted by Mrs. Aisyah (tomato farmer) to produce candied tomatoes. This research was conducted using the mentoring method, by means of which the researchers held discussions with tomato farmers and conducted evaluations from the initial process to the final process of making candied tomatoes. Based on the results of the activity, it is known that the involvement and active participation of partners is very high in every implementation of the candied tomato making program. So that with the production of tomatoes into candied tomatoes, it can increase the development of Mrs. Aisyah's income and provide opportunities for people who do not have a job to serve as partners in the process of making and selling candied tomatoes.